AN ANALYSIS OF LEADERSHIP AND STRUGGLE IN THE 2026 UNITED STATES–VENEZUELA CONFLICT TO ENHANCE THE CAPABILITIES OF THE INDONESIAN NAVY IN DEVELOPING OPERATIONAL STRATEGIES - Wantoro, Sabono; Ilham, Muh.; Prasetiadi, Ferry (Journal of Industrial Engineering & Management Research, 2026)
— This study examines the 2026 conflict between the United States and Venezuela through the lenses of transformational leadership, realism in international relations, crisis decision-making, and asymmetric warfare. Using a qualitative method, the research analyzes the chronology of the conflict from the pre-crisis phase, the outbreak of military confrontation, and its post-conflict regional and global repercussions. The findings show that the conflict was driven by the intersection of geopolitical rivalry, energy security, military pressure, and ideological contestation. From a leadership perspective, Donald Trump and Nicolás Maduro demonstrated contrasting but equally decisive leadership styles in responding to crisis conditions. From a realist perspective, the conflict reflected the pursuit of national interests, power projection, and the struggle to preserve regional influence. The study also finds that crisis decision-making under time pressure and uncertainty shaped rapid strategic choices on both sides, while Venezuela’s response illustrated the relevance of asymmetric warfare in confronting a militarily superior adversary. Furthermore, the conflict generated humanitarian, diplomatic, and energy-related consequences that extended beyond the two states. For Indonesia, particularly the Navy, the case offers important lessons on maritime readiness, joint operations, defense diplomacy, and post-conflict stabilization.